Development of novel transparent radiation shielding glasses by BaO doping in waste soda lime silica (SLS) glass - Khazaalah, Thair Hussein; Mustafa, Iskandar Shahrim; Sayyed, M. I.; Abdul Rahman, Azhar; Mohd Zaid, Mohd Hafiz; Hisam, Rosdiyana; Abdul Malik, Muhammad Fadhirul Izwan; Ezra, Nabasu Seth; Naeem, Hayder Salah; Che Khalib, Nuridayanti (MDPI, 2022)
In the current study, BaO was doped in Bi2O3-ZnO-B2O3-SLS glass to develop lead-free radiation shielding glasses and to solve the dark brown of bismuth glass. The melt-quenching method was utilized to fabricate (x) BaO (1 − x)[0.3 ZnO 0.2 Bi2O3 0.2 B2O3 0.3 SLS] (where x are 0.01, 0.02, 0.03, 0.04, and 0.05 mol) at 1200 °C. Soda lime silica glass waste (SLS), which is mostly composed of 74.1% SiO2, was used to obtain SiO2. The mass attenuation coefficient (μm) was investigated utilizing X-ray fluorescence (XRF) at 16.61, 17.74, 21.17, and 25.27 keV and narrow beam geometry at 59.54, 662, and 1333 keV. Moreover, the other parameters related to gamma ray shielding properties such as half-value layer (HVL), mean free path (MFP), and effective atomic number (Z e f f) were computed depending on μm values. The results indicated that HVL and MFP decreased, whereas μm increased with an increase in BaO concentration. According to these results, it can be concluded that BaO doped in Bi2O3-ZnO-B2O3-SLS glass is a nontoxic, transparent to visible light, and a good shielding material against radiation.